STRATEGI GURU DALAM MENGATASI KETERBATASAN SARANA DAN PRASARANA PADA PEMBELAJARAN BERBASIS BERMAIN DI TAMAN KANAK-KANAK - Safaatur Rosydah; Siti Mariah Ulfa; Nurlinda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the limited facilities and infrastructure that pose obstacles to the implementation of play-based learning at Harapan Ibu Kindergarten in Ngaol Village, Tabir Barat Subdistrict, Merangin Regency. These conditions require teachers to employ various strategies to ensure that the learning process remains effective, engaging, and appropriate for the characteristics of young children. This study aims to describe the condition of available facilities and infrastructure, analyze the strategies teachers use to overcome these limitations, and explain the use of simple learning media and the surrounding environment as alternative learning resources. The study employs a qualitative approach using a descriptive research design. The research subjects consist of the principal, teachers, and students. Data were collected through observation, interviews, and documentation, then analyzed using the stages of data reduction, data presentation, and drawing conclusions. The results showed that teachers implemented various strategies, including utilizing natural materials and recycled items as learning media, modifying available educational toys, optimizing the surrounding environment as a learning resource, and designing creative play activities tailored to children’s developmental needs. Supporting factors included teacher creativity, support from the school principal, and the utilization of the surrounding environment, while inhibiting factors included budget constraints, a lack of learning facilities, and a shortage of educational toys. These strategies proved effective in supporting the implementation of play-based learning even under conditions of limited facilities and infrastructure